The Role of Entrepreneurial Orientation in Shaping the Performance of Micro, Small and Middle-sized Enterprises - Suder, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2023)
Objective: To identify the configuration of the dimensions of entrepreneurial orientation (risk-taking, innovativeness and proactiveness), which lead to high enterprise performance; to identify differences in this regard between micro, small and medium-sized enterprises.Research Design & Methods: The study employed a fuzzy-set qualitative comparative analysis (fsQCA). This method was applied separately for three types of enterprises – micro, small and medium-sized. The research used data obtained from 430 companies operating in Poland’s Małopolska region.Findings: The results showed that two combinations of factors – risk-taking with proactivity and proactiveness with innovativeness – can lead to improved performance in small enterprises. In medium-sized enterprises, the combination of proactiveness and innovativeness can improve results. The combination of risk-taking and proactiveness leads to higher results in micro-enterprises.Implications / Recommendations: The results confirm the importance of an entrepreneurial orientation and its various dimensions in improving company performance. In addition, the results indicate that the combinations of factors leading to high performance differ depending on company size.Contribution: The study contributes to a better understanding of the impact of entrepreneurial orientation on a firm’s performance and the functioning of SMEs.